Improving the combat capability of small police tactical groups - I. V. Vlasenko; I. P. Lykhyi; Ya. O. Slatin (Law and Safety)
The article analyses the methods of enhancing the combat capability of small police tactical groups, in particular, with regard to their participation in hostilities during martial law in Ukraine. The main attention is paid to the importance of the optimal location of the commander in a small tactical group, which ensures the efficiency of performance of service and combat tasks, prompt decision-making, mobility and security of the group.